27‐hydroxycholesterol promotes oligodendrocyte maturation: Implications for hypercholesterolemia‐associated brain white matter changes. Issue 6 (13th February 2023) - Alanko, Vilma; Gaminde‐Blasco, Adhara; Quintela‐López, Tania; Loera‐Valencia, Raúl; Solomon, Alina; Björkhem, Ingemar; Cedazo‐Minguez, Angel; Maioli, Silvia; Tabacaru, Graziella; Latorre‐Leal, María; Matute, Carlos; Kivipelto, Miia; et al.
Abstract: Oxidized cholesterol metabolite 27‐hydroxycholesterol (27‐OH) is a potential link between hypercholesterolemia and neurodegenerative diseases since unlike peripheral cholesterol, 27‐OH is transported across the blood–brain barrier. However, the effects of high 27‐OH levels on oligodendrocyte function remain unexplored. We hypothesize that during hypercholesterolemia 27‐OH may impact oligodendrocytes and myelin and thus contribute to the disconnection of neural networks in neurodegenerative diseases. To test this idea, we first investigated the effects of 27‐OH in cultured oligodendrocytes and found that it induces cell death of immature O4 + /GalC + oligodendrocytes along with stimulating differentiation of PDGFR + oligodendrocyte progenitors (OPCs). Next, transgenic mice with increased systemic 27‐OH levels (Cyp27Tg) underwent behavioral testing and their brains were immunohistochemically stained and lysed for immunoblotting. Chronic exposure to 27‐OH in mice resulted in increased myelin basic protein (MBP) but not 2′, 3′‐cyclic‐nucleotide 3′‐phosphodiesterase (CNPase) or myelin oligodendrocyte glycoprotein (MOG) levels in the corpus callosum and cerebral cortex. Intriguingly, we also found impairment of spatial learning suggesting that subtle changes in myelinated axons of vulnerable areas like the hippocampus caused by 27‐OH may contribute to impaired cognition. Finally, we found that 27‐OH levels in cerebrospinal fluid from memory clinic patients were associated with levels of the myelination regulating CNPase, independently of Alzheimer's disease markers. Thus, 27‐OH promotes OPC differentiation and is toxic to immature oligodendrocytes as well as it subtly alters myelin by targeting oligodendroglia. Taken together, these data indicate that hypercholesterolemia‐derived higher 27‐OH levels change the oligodendrocytic capacity for appropriate myelin remodeling which is a crucial factor in neurodegeneration and aging. Main Points: High 27‐hydroxycholesterol (27‐OH) levels alter myelin protein levels and oligodendrocyte maturation. 27‐OH levels in cerebrospinal fluid from memory clinic patients associate with CNPase.